Effect of Polishing Systems on Fluoride Release and Surface Roughness of Different Restorative Materials - Soner Şişmanoğlu (Odovtos - International Journal of Dental Sciences, 2020)
Secondary caries is an important factor in the replacement of the restorations, and it is thought that fluoride-releasing materials may prevent this problem. Furthermore, the fluoride release of the materials may be increased by polishing process. Available knowledge about the effect of polishing systems (PS) on the fluoride release of materials is limited. Therefore, this study was conducted to evaluate the effect of PS on the fluoride release of fluoride-containing materials. Restorative materials were divided into 6 groups: Fuji IX GP, Fuji II, Dyract XP, Beautifil II, Beautifil-Bulk, and Filtek Ultimate. Each group was also divided into four subgroups: Mylar strip, Sof-Lex Discs, Sof-Lex Diamond, and OneGloss. Fluoride release was determined using a fluoride ion-selective electrode. Surface roughness was evaluated with a profilometer. Two- way repeated measure and one-way ANOVA tests were used for statistical analysis. The initial rapid fluoride release was observed only in Fuji IX. The PS increased the fluoride release of Fuji IX and Fuji II and Dyract XP materials while reducing the fluoride release of resin-based materials. The highest surface roughness values were obtained with OneGloss. Further, a significant relationship between fluoride release and surface roughness was found. The polishing provides an increase in fluoride release, especially in glass-ionomer-based materials. This article revealed that there is a relationship between fluoride release and surface roughness. Proper PS must be chosen according to the material to provide the best clinical benefits in terms of fluoride release and surface roughness.